'No hint of bulging muscles': The surveillance of sportswomen's bodies in British print media. (August 2016) - Godoy-Pressland, Amy
Since the inception of second wave feminism, feminists have placed female bodies at the centre of the equality discourse. The female body is a contested site for feminist scholars who have identified the under- and mis-representation of sportswomen's bodies in the media. This article investigates how surveillance techniques are employed in British Sunday newspapers as a function of hegemonic power to influence gendered notions of sport and the display of female bodies in line with normative femininity. Data stem from a semi-longitudinal study which analysed the quantitative and qualitative representation of sportswomen in British print media during January 2008–December 2009. Foucault's analysis of the Panopticon and Mulvey's concept of 'gaze' are used to interpret the data through the lens of surveillance. Findings demonstrate how the surveillance of female sporting bodies occurred in four distinct ways. The categories, which emerged from the data, include the body as (1) trivialised, (2) secondary, (3) commercial and (4) feminine.